Memo - Intelligence Dept, 11 May 1926, re: New Emergency Power Regulations 9 May 1926
1926-05-11 "Memo - Intelligence Dept, 11 May 1926, re: New Emergency Power Regulations 9 May 1926" [g0790001.jpg], 11 May 1926 TUC Organisation